Scripta Bulgarica: Digital Library of the Medieval Bulgarian Literature - Милтенова, Анисава (Slavistica Vilnensis, 2018)
[full article, abstract in English; abstract in Lithuanian and Russian]The project “SCRIPTA BULGARICA: Digital Library of Medieval Bulgarian Literature” (http://www.scripta-bulgarica.eu/en ) is intended to create an electronic thesaurus and a library of Old Church Slavonic written tradition integrating three main types of information: a) terminology in the field of palaeoslavic studies — both in the existing scientific literature and in the successfully functioning digital corpuses; b) encyclopaedic articles about translated and original works outlining the most popular genres and genre forms in hagiography, homiletics, hymnography, chgronicles, narrative works and others; c) transcribed texts in Unicode from Slavonic manuscripts representing the translated literature from Byzantine Greek; d) articles about the most frequently translated Byzantine authors (e.g. Gregory the Theologian, St. John Chrysostom, St. Basil the Great, etc.), whose works (genres and genre forms) modeled and formed Orthodox Christian written culture. The articles for terminology include glossary in 7 languages: Latin, Greek, Old Church Slavonic, Russian, Serbian, English, German. Main information is in Bulgarian. The SCRIPTA BULGARICA project also includes a unique for such initiatives in the humanities connection between the generated standardized apparatus for description, research, publication and translation of medieval texts with the keywords and the bibliography. This allows the integration of the apparatus of scientific metadata in a uniform entity and the advanced stage of the project will see the development of an ontology of terms.
Keywords: thesaurus, terms in palaeoslavic studies, integrated digital corpus, Unicode, Drupal